The role of vitamin A in non-ruminant immunology - Shastak, Yauheni; Pelletier, Wolf (Frontiers in Animal Science, 2023)
Vitamin A (retinol) is an essential micronutrient with a crucial role in the immune system of nonruminant animals, such as swine and poultry. It includes three chemical compounds with distinct properties and functions in the body: retinol, retinal, and retinoic acid. In monogastric feed, vitamin A is primarily present in the form of retinyl esters. The metabolism of dietary vitamin A esters involves their conversion to retinol, which is then transported to different tissues and cells for further metabolism into active forms such as retinoic acid. These active forms of vitamin A have been found to play a crucial role in regulating both innate and adaptive immune responses. Specifically, they are involved in the differentiation, proliferation, and function of immune cells such as T and B lymphocytes, as well as dendritic cells. Vitamin A deficiency can lead to impaired cellular immunity, reduced antibody production, and consequently an increased susceptibility to infections. In swine and poultry, hypovitaminosis A can also affect gut-associated lymphoid tissues, leading to gut-related health problems and compromised growth performance. On the other hand, vitamin A supplementation has been shown to have immunomodulatory effects on non-ruminant immune responses. By administering or supplementing retinol, immune cell proliferation, antibody production, and cytokine secretion can be enhanced, which can ultimately result in improved immune function and disease resistance. Therefore, vitamin A has potential applications as an immunomicronutrient for improving health and preventing diseases in swine and poultry. However, the optimal dosage and timing of vitamin A supplementation need to be carefully determined based on the specific requirements of different non-ruminant species and their production stages. Overall, a better understanding of the role of vitamin A in non-ruminant nutritional immunology could have significant implications for animal health and productivity and could inform the development of effective dietary strategies to optimize immune function and prevent diseases in swine and domestic fowl. This review paper aims to offer valuable insights into the role of vitamin A in the nutritional immunology of non-ruminants while also emphasizing the current gaps in knowledge and potential areas for further research.